Analisis Kepemimpinan Visioner Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di Taman Kanak-Kanak Pertiwi 12 Gading - Sari, Diana Nofita; Margarani, Ika Purnamasari; Syahrani, Rahmalia Addin (TARBIYAH: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This research aims to analyze the role of the school principal’s visionary leadership in improving teacher performance at Pertiwi 12 Gading Kindergarten. The method in this research is a qualitative approach to descriptive research design. Data collection was carried out through interviews, observation and documentation involving school principals and teacher. The research results show that the principal applies an effective visionary leadership style as a direction setter, change agent, spokesperson, and coach. The application of this visionary leadership has a positive impact on teacher performance through professional abilities, social abilities and personal abilities. Then, there are supporting factors that play a role in the success of visionary leadership, such as good communication with stakeholders, teachers’ desire to develop the school, parental support, professional development training, and adequate infrastructure. However, there are inhibiting factors such as limited human resources, budget shortages, excessive workload and lack of support from related parties.